2023
DOI: 10.3390/ijerph20020997
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Behaviours among Food Handlers in Different Food Service Establishments in Montenegro

Abstract: Foodborne diseases in food facilities are a major public health problem, due mostly to the limited surveillance and educational level of food-handling workers. This study was conducted in 220 food service locations in Montenegro. Participants’ behaviour was assessed by a survey using the specifically designed structured questionnaire, administered before and after the training. To determine the effect of the training on the performance of food handlers, a microbiological analysis of food contact surfaces and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Even after cleaning, there is always a lingering concern about allergens from the previous use." In this case, Labović et al (2023) suggested that education significantly contributes to improving how individuals who handle food manage it, consequently decreasing the chances of food contamination. Pastry equipment is used for various ingredients and products, increasing the risk of cross-contamination if not cleaned properly between uses.…”
Section: Risk Of Cross-contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after cleaning, there is always a lingering concern about allergens from the previous use." In this case, Labović et al (2023) suggested that education significantly contributes to improving how individuals who handle food manage it, consequently decreasing the chances of food contamination. Pastry equipment is used for various ingredients and products, increasing the risk of cross-contamination if not cleaned properly between uses.…”
Section: Risk Of Cross-contaminationmentioning
confidence: 99%
“…When it comes to food processing, the repercussions of deviating from established procedures reverberate across various facets of public health and safety. A significant concern arising from non-compliance is the heightened risk of food contamination, as highlighted by Labović et al (2023). This contamination can stem from various sources, including improper handling, inadequate storage, or faulty equipment, potentially leading to detrimental consequences for consumers.…”
Section: Optimizing the Hygiene And Sanitation Practicesmentioning
confidence: 99%
“…Berdasarkan kajian yang dijalankan oleh Jevšnik et al (2021), punca utama pengendali perkhidmatan makanan untuk mengamalkan kebersihan dalam penyediaan makanan adalah kekurangan pengetahuan dan kekurangan kemahiran kebersihan makanan. Selain itu, hasil kajian Labović et al (2023) mendapati bahawa tingkah laku pengendali makanan terhadap kebersihan diri dan pengendalian makanan adalah tidak memuaskan. Hal ini sangat membimbangkan kerana ianya boleh menjadi punca penyebaran wabak penyakit bawaan makanan.…”
Section: Skala Tempahan > 500 Hidanganunclassified
“…The technological trends of Montenegrin manufacturing are reviewed by Vujanović [50], and Boban et al [51] studied the competitiveness of homemade consumables. Labović et al [52] studied food safety in Montenegrin restaurants and other food service establishments, Rajović and Bulatović [53] investigated plant-and animal-based food production, and Martinovic and Mirecki [54] analyzed their connection to health in the country. Tourism is addressed by the works of Jaksic-Stojanovic et al [55], Moric et al [56,57], and Bigović [58], highlighting sports, cultural and rural tourism, and its seasonality.…”
Section: Introductionmentioning
confidence: 99%